Access to medicines through global health diplomacy - Vijay Kumar Chattu; Bawa Singh; Sanjay Pattanshetty; Srikanth Reddy (Tabriz University of Medical Sciences, 2023)
The World Health Organisation (WHO) emphasizes that equitable access to safe and affordable medicines is vital to attaining the highest possible standard of health by all. Ensuring equitable access to medicines (ATM) is also a key narrative of the Sustainable Development Goals (SDGs), as SDG 3.8 specifies "access to safe, effective, quality and affordable essential medicines and vaccines for all" as a central component of universal health coverage (UHC). The SDG 3.b emphasizes the need to develop medicines to address persistent treatment gaps. However, around 2 billion people globally have no access to essential medicines, particularly in lower- and middle-income countries. The states' recognition of health as a human right obligates them to ensure access to timely, acceptable, affordable health care. While ATM is inherent in minimizing the treatment gaps, global health diplomacy (GHD) contributes to addressing these gaps and fulfilling the state's embracement of health as a human right.